2019
DOI: 10.1136/bmjresp-2019-000468
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and healthcare delays among people with tuberculosis in London, and the impact on treatment outcome

Abstract: BackgroundA quarter of London’s pulmonary tuberculosis (TB) patients have over 4 months of delay. Late diagnosis increases disease severity and the risk of transmission. We aim to classify delays, identify associated risk factors and assess treatment outcome.MethodsWe conducted a retrospective cohort study using London surveillance data, 2012–2018 on adults aged ≥18 years with pulmonary TB. We defined presentation delay (days from symptom onset to first healthcare visit) and healthcare delay (first healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…We presume that TB could have been prevented in many exposed children through timely identification of the source case. Delayed diagnosis of pulmonary TB is frequently reported in high TB-incidence low-and middle-income countries [29], but also in low-incidence countries [30,31]. Furthermore, transmission prior to TB symptoms in subclinical source cases may occur [32]; thus, documented exposure times may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…We presume that TB could have been prevented in many exposed children through timely identification of the source case. Delayed diagnosis of pulmonary TB is frequently reported in high TB-incidence low-and middle-income countries [29], but also in low-incidence countries [30,31]. Furthermore, transmission prior to TB symptoms in subclinical source cases may occur [32]; thus, documented exposure times may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the health delay between males and females and individuals older and younger than 64. The literature seems to indicate that older age is associated with higher delays [ 26 , 27 ]. However, other studies found no association, which could be due to different classifications of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found no association, which could be due to different classifications of age. Some considered age as above 60, 70, or distinct age groups [ 9 , 23 , 26 , 27 ]. We found that females had significantly higher health delays than males in most regions, which was replicated in other studies [ 23 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) The results of a relevant study in London also showed that social factors affected the delay in the diagnosis and treatment of TB. (8) On the other hand, a person with TB expects psychological support and guidance from his caregiver. In patient's view, home is a proper place for rest and recovery.…”
Section: Introduction Dmentioning
confidence: 99%